Correlative characterization on microstructure evolution of Ni-based K403 alloy during thermal exposure. (1st June 2017) - Liu, Jun; Li, Jiehua; Hage, Fredrik S.; Ghosh, Pradipta; Li, Jun; Wang, Wei; Chen, Zongning; Wang, Tongmin; Tang, Wenting; Ramasse, Quentin; Schumacher, Peter
Abstract: The microstructure evolution of the K403 Ni-based superalloy as a function of thermal exposure temperature and time was investigated using correlative characterization, including a combination of scanning electron microscopy, electron backscatter diffraction, transmission electron microscopy, high-angle angular dark-field scanning transmission electron microscopy imaging and electron energy loss spectroscopy. The as-cast microstructure of the K403 alloy shows a typical dendritic structure and consists of a γ solid solution, γ′ phase, ( γ + γ′ ) eutectic phase and a metal carbide (MC) phase. The solutes of Ni and Ti are enriched in the γ solid solution, while, the solutes of Cr and Co are enriched in the γ′ phase. The morphology of the γ′ phase is nearly cubic. After thermal exposure at 800 °C or 950 °C for up to 200 h, the typical dendritic structure and a similar solute segregation behavior were still observed. However, the MC carbides were partially decomposed and further transformed to the M6 C phase and M23 C6 phase. Furthermore, the size of γ′ was increased from 302.88 ± 20.49 nm to 374.75 ± 29.76 nm (800 °C, 50 h) and 751.73 ± 123.14 nm (950 °C, 50 h), respectively. The morphology of γ′ was changed from cubic to triangular or round. Clearly, there is a significant coarsening of γ′ during thermal exposure. A topologically close-packed (TCP) σ phase was observed after thermal exposure at 800 °C for 100 h or 950 °C for 50 h. More interestingly, an in-situ phase transformation of the σ phase to other TCP phase (i.e. P phase) was also observed after thermal exposure at 950 °C for 50 h. The formation and transformation of carbide (i.e. M6 C phase, M23 C6 phase) and TCP phases (i.e. σ phase, P phase) is proposed to be a diffusion-controlled process and can be attributed to the solute diffusion during thermal exposure. The present investigation provides a better understanding on the high temperature performance of the K403 Ni-based superalloy, which is essential to predict the failure and thereby enhance the reliability and service life of the K403 Ni-based superalloy. Graphical abstract: Image 1